Pengembangan Media Pembelajaran Interaktif Pada Konsep Monera Berbasis Smartphone Android - Gufron Amirullah; Susilo Susilo (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2018)
This study aims to develop media learning of Android-based mobile for students of Senior High School class X, and to know the quality of mobile media learningproducts on the concept of monera. The research was done through 2 stages, namely Preliminary and Formative Evaluation. Formative Evaluation Phase was divided into 3 stages namely, Self-Evaluation, Prototyping and Field Test. Validation was done by material experts and media experts. The developed media was tested to 100 students of class X IPA SMAN 5 Bekasi. Data analysis techniques were used the feasibility and quality of media obtained with the instrument in the form of a questionnaire. The results showed that the value of media-based learning feasibility of Android-based monera of 93.92% with Excellent category and material expert judgment of 97% with Excellent category. Trial on students at SMAN 5 Bekasi school obtained the quality of media learning is 91.40% with Excellent category. Based on the results of data acquisition shows that learning media based on Android mobile learning on the concept of monera worthy of use as a source of learning class X high school students.